Familiárna stredomorská horúčka - klinický obraz, diagnóza a liečba - Dallos, Tomáš; Ilenčíková, Denisa; Kovács, László (Vnitrni lekarstvi, 2014)
Familial mediterranean fever (FMF) is the most prevalent genetically determined autoinflammatory disease. FMF significantly decreases the quality of life and limits life expectancy due to the development of amyloidosis in affected individuals. Prevalence of FMF is highest in the south-eastern Mediterraneans. In other parts of the world, its occurance is often restricted to high-risk ethnic goups. In Central Europe, experience with FMF is scarse. As for Slovakia, we have reported the first cases of FMF in ethnic Slovaks only recently. Along with their complicated fates, this has lead us to compile a comprehensive overview of the clinical picture, diagnosis and treatment of this elusive disease. Hereby we hope to be able to promote the awareness about this disease and possibly aid the diagnosis in new patients.
Keywords: Slovenská republika; familiární středomořská horečka; Slovakia; Female; Prevalence; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; Familial Mediterranean Fever; lidé středního věku; Europe; Middle Aged; Evropa; prevalence